Sulphur dioxide fluxes from Mount Etna, Vulcano, and Stromboli measured with an automated scanning ultraviolet spectrometer - McGonigle, A; Oppenheimer, C; Hayes, A; Galle, B; Edmonds, M; Caltabiano, T; Salerno, G; Burton, M; Mather, T (2003)
We report here SO2 flux measurements for the southern Italian volcanoes: Mount Etna, Vulcano, and Stromboli made in July 2002 from fixed positions, using an automated plume scanning technique. Spectral data were collected using a miniature ultraviolet spectrometer, and SO2 column amounts were derived with a differential optical absorption spectroscopy evaluation routine. Scanning through the plume was enabled by a 45° turning mirror affixed to the shaft of a computer controlled stepper motor, so that scattered skylight from incremental angles within the horizon-to-horizon scans was reflected into the field of view of the spectrometer. Each scan lasted ∼5 min and, by combining these data with wind speeds, average fluxes of 940, 14, and 280 Mg d-1 were obtained for Etna, Vulcano, and Stromboli, respectively. For comparative purposes, conventional road and airborne traverses were also made using this spectrometer, yielding fluxes of 850, 17, and 210 Mg d-1. The automated scanning technique has the advantage of obviating the need for time-consuming traverses underneath the plume and is well suited for longer-term telemetered deployments to provide sustained high time resolution flux data.